Novel V2O5/BiVO4/TiO2 nanocomposites with high visible-light-induced photocatalytic activity for the degradation of toluene - Sun, J.; Li, Xin Yong; Zhao, Q.; Ke, J.; Zhang, D. (American Chemical Society, 2014)
In an effort to develop nanostructured photocatalysts to achieve high performance in heterogeneous photocatalysis, a novel composite V 2O5/BiVO4/TiO2 photocatalyst was successfully synthesized by using a sequentially hydrothermal and adhering method. The structural and optical properties of the as-prepared samples were comparatively characterized. The formed ternary nanojunctions were composed of TiO2 nanobelts and V2O5/BiVO4 nanorods which were self-assembled by smaller V2O5 and BiVO4 nanoparticles. Compared to pure TiO2 nanobelts and V2O5/BiVO4 nanorods, the V2O 5/BiVO4/TiO2 composite exhibited higher photocatalytic activity in decomposition of gaseous toluene under visible light irradiation (> 400 nm). Electron spin resonance examination confirmed that the photoinduced active species (•OH and O2 •-) were involved in the photocatalytic degradation of toluene. A detailed mechanism accounting for the enhanced photocatalytic activity of the V2O5/BiVO4/TiO2 nanocomposite was proposed in terms of the energy band structures of the components. The rationally designed ternary nanojunctions could effectively enhance the photocatalytic performance by increasing photoinduced charge carriers through the charges separation across their multiple interfaces. © 2014 American Chemical Society.